Do Longer School Days Improve Student Achievement? Evidence from Colombia - Diana Hincapie (Inter-American Development Bank (IDB), 2016)
This paper analyzes the impact of longer school days on student achievement in Colombia. To identify the impact of longer schools days, this study exploits plausibly exogenous within school variation in the length of the school day. Using test score data from 5th and 9th graders in 2002, 2005, and 2009, along with school administrative data, this research uses school fixed effects models to estimate variation in average test scores across cohorts for schools that switched from a half school day to a full school day or vice versa. It finds that cohorts exposed to full school days have test scores that are about one tenth of a standard deviation higher than cohorts that attended half school days. The impact of attending full school days is larger for math than for language, and it is larger for 9th grade than for 5th grade. Effects are largest among the poorest schools and those in rural areas. The results suggest that lengthening the school day may be an effective policy for increasing student achievement, particularly for the lowest-income students in Colombia and other developing countries.
hdl:11319/7545
Keywords: I21; I28; H43; 330; quality of education; student achievement; instructional time; school day